Pemanfaatan Literasi Sebagai Media Pembelajaran Kemampuan Membaca Permulaan Anak Usia Dini - Dewi, Utami Kumala; Hibana (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2024)
Supporting the optimization of early literacy is crucial for developing language skills. Reading at an early age is often called early reading. Therefore, this study aims to determine how literacy facilities are used to learn early reading skills, especially for the 5-6-year-old age group. Primary data was collected through observation, interviews, and activity documentation, while secondary data sources were obtained from literature reviews. Data analysis followed Miles and Huberman's, which involves identifying and describing the main problem, categorizing data according to the discussion, presenting and analyzing data descriptively, and drawing conclusions about the main problem. The researcher used a qualitative research method with a descriptive approach. The research subjects were group B of TK Islam Terpadu Salsabila 5 Purworejo, totaling 25 students, one classroom teacher, and the principal. The results of this study indicate that the TK Islam Terpadu Salsabila 5 Purworejo institution introduces early reading through (1) Literacy corner and pre-reading routines; (2) Natural materials/loose part methods; (3) Electronic media (laptops) and storytelling method; (4) Tracing, sticking, and imitating words. These learning media are expected to facilitate students' learning and help them recognize early reading. The facilities provided are excellent and helpful, and it is hoped that in the future, electronic media (laptops) will be presented via an LCD screen to accommodate all students.